Professional Development and Learning of Teacher Educators - Case Study of a Community of Practice (CoP) Formed During the COVID-19 Pandemic in India - Ramchand, Mythili; Chatterji, Ananya; Jatin, Gomathi; Thirumalai, Bindu; Thomas, Sybil (Voices of Teachers and Teacher Educators, 2023)
Communities of Practice (CoP) have been recognised globally as a potential tool to support teacher educators’ professional learning. This paper reports the formation of a virtual, inter-institutional community of practice (CoP) of 278 prospective and practising teacher educators in India during the COVID-19-induced lockdown in 2020. Using an online survey, focus group discussions, and inteiews, the paper presents the challenges in the profession identified by teacher educators, their needs and expectations from the CoP, their perceptions about the CoP’s contributions towards their own learning, and the extent of their engagement over four months with the CoP. There were 68 respondents to the survey, of which 33 were practising teacher educators. They recognised the potential of CoP as a space to enhance their own learning. Through their participation in the CoP, teacher educators reported gaining confidence in engaging with current educational discourses, sharing ideas and practices, and trying out different pedagogical approaches. They identified poor status, pay and working conditions, inadequate opportunities for professional development, and limited access to academic networking as key challenges. The study indicates that virtual CoPs have the potential to modify and bring about learning in a diverse group of people through mutual engagement.